TRENDS IN AGRICULTURE ENDOWMENT WITH MACHINERY IN ROMANIA 2007-2015 - Agatha POPESCU; Toma DINU; Elena STOIAN; Ionela Mituko VLAD (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper goal was to analyze the technical endowment in terms of machinery in Romania's agriculture in the period 2007-2015 and to identify the main trends and problems which affect performance and competitiveness. In the analyzed period, the park of tractors and machinery increased as follows: tractors by 14.5 %, ploughs by 13.9 %, cultivators by 11.3 %, seeders by 14.6 %, combines for cereals by 11.4 and for fodder by 17 %, machines for potatoes harvesting by 43.5 %, presses for hay and straw by 121.7 %, only windrowers and sprayers and dusters declined by 1.2 %, respectively, by 2.6 %. Despite this slight increase, the structure of agricultural machinery is still an uncorresponding one for keeping pace with new technologies. The utilized agricultural area (UAA) increased and as a result the UAA per tractor declined from 44.5 ha to 41.3, which is also a good aspect. Despite that agricultural production increase, its performance is not supported by mechanization mainly in the small sized holdings. The replacement of the existing old machinery with a high usage degree, whose repairs are costing, is obviously needed and requires substantial financial resources. the continuous growth of farm inputs price and the low price at farm gate for agricultural products do not assure farmers enough income to modernize mechanization. The Romanian Government should allocate a higher percentage from budget to agriculture for improving the park of tractors and agricultural machinery. Also, the financial aid per ha coming from the EU should be equitably divided among member states. Farmers need a better endowment in their farms to apply modern technologies and increase production, quality of agricultural products, economic efficiency and competitiveness.